ANALISA BAHAYA DAN RISIKO KECELAKAAN KERJA PADA PEMELIHARAAN ALAT CONTAINER CRANE (CC) - Putri, Santa; Assidiq, Fuad Mahfud (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2022)
The port is a workplace that has a high risk of accidents, one of which is for loading and unloading activities using lifting equipment. The operation of lifting equipment such as Container crane (CC) is an activity that must receive attention to safety in addition to loading and unloading activities at the port because there are risks that have the potential to cause serious work accidents. Container cranes (CC) often also called Quayside Cranes or Gantry Cranes are loading and unloading equipment that functions to unload or load containers from ships to docks / land. This study aims to determine the identification of hazards and risks of work accidents in the maintenance of Container crane (CC) equipment. Risk assessment of each work activity on the Container crane (CC) tool obtained 4 accident risks, namely three high risk categories, three moderate risk categories, and one low risk category.